Kontribusi Instrumen Pasar Modal Syariah terhadap Pendanaan Infrastruktur Hijau di Indonesia - Ayu Wulandari S. Tanjung; Marliyah Marliyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to see how sharia capital market instruments contribute to green infrastructure funding in Indonesia. This research is library research which analyzes the contribution of the sharia capital market, especially through instruments such as green sukuk, to the acceleration of green infrastructure development in Indonesia. From the research results, it is known that the contribution of the sharia capital market to accelerating green infrastructure development lies in its ability to provide sharia-based financing for environmentally friendly projects. Through instruments such as green sukuk, the Islamic capital market supports renewable energy projects, sustainable transportation and natural resource management. By meeting long-term financing needs, the Islamic capital market helps accelerate the realization of green infrastructure that supports sustainability goals, including Sustainable Development Goals (SDGs), and reduces the impact of climate change.